Penerapan Jaminan Fidusia dalam Akad Murabahah Pembiayaan Oto Pada Bank Syariah Indonesia Cabang Cirebon - Sintya Fakhrunisa; Muhit, Ryan Abdul (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2023)
In today's life will not escape all the needs and desires to buy an item. For this reason, Murabaha is a form of buying and selling with a commission, the buyer usually cannot get the goods he wants except through an intermediary. In the purchase of a vehicle there is a fiduciary guarantee, fiduciary is goods by the debtor entrusted to the creditor as debt guarantee. However, in its implementation there are problems with traffic jams that can harm the debtor or creditor. The method used in this research is qualitative which produces descriptive data, namely what is stated by the respondents in writing, verbally and real behavior. The results of this study are the procedure for applying for financing on BSI products with murabahah contracts that make it easier for the community to access them, friendly, kind and honest service. The execution of fiduciary guarantees is the final solution for customers who are in arrears by conducting auctions of collateral objects. The application is in accordance with the DSN-MUI Fatwa No. 04/2000 and compilation of Sharia Economic Law.